Gambaran Perilaku Wanita Usia Subur (Wus) dalam Upaya Deteksi Dini Kanker Serviks dengan Metode Acetic Acid Visual Inspection (IVA) di Wilayah Kerja Puskesmas Simpang Baru - Yos Bayu Apriliano; Sri Utami; Arneliwati Arneliwati (Universitas Harapan Bangsa Purwokerto, 2022)
Cervical cancer is a major health problem in women in the world, cervical cancer can be prevented by early detection, one of which is the VIA examination. According to data from the Pekanbaru city office in 2019, there were 5 people carrying out an IVA examination at the Simpang Baru Health Center. Factors that influence WUS in the IVA examination behavior are knowledge, attitudes and actions. This study aims to describe the behavior of WUS in an effort to detect cervical cancer using the IVA method in the work area of the Simpang Baru Health Center. Methodology on this research was a quantitative descriptive. The sample in this research were 100 respondents who live in Simpang Baru with propotional random Sampling technique. The variables in this study are behavior with the variable domains of knowledge, attitudes and actions. Measuring instruments used was a questionnaire. The analysis used was univariate. The results of the study based on WUS behavior, it was found that respondents with a row level of knowledge about cervical cancer and early detection efforts were (65%), respondents had a bad attitude about early detection efforts (54%), most of the respondents did not want to take early detection efforts. cervical cancer (54%). and WUS behavior is categorized as negative (61,0%). Behavior will be realized if high knowledge is followed by good attitudes and good actions, therefore it is recommended to increase promotion and counseling about cervical cancer and early detection efforts, so that it will increase awareness and willingness to improve health behavior in efforts to detect cervical cancer early with the IVA method. The conclusion of the study is that most respondents have low knowledge, bad attitudes, do not want to do early detection and negative WUS behavior towards knowledge of early detection of cervical cancer